Meisoindigo Protects Against Focal Cerebral Ischemia-Reperfusion Injury by Inhibiting NLRP3 Inflammasome Activation and Regulating Microglia/Macrophage Polarization via TLR4/NF-κB Signaling Pathway - Ye, Yingze; Jin, Tong; Zhang, Xu; Zeng, Zhi; Ye, Baixin; Wang, Jinchen; Zhong, Yi; Xiong, Xiaoxing; Gu, Lijuan (Frontiers in Cellular Neuroscience, 2019)
Ischemic stroke is a devastating disease with long-term disability. However, the pathogenesis is unclear and treatments are limited. Meisoindigo, a second-generation derivative of indirubin, has general water solubility and is well tolerated. Previous studies have shown that meisoindigo reduces inflammation by inhibiting leukocyte chemotaxis and migration. In the present study, we investigated the hypothesis that meisoindigo was also protective against ischemic stroke, then evaluated its underlying mechanisms. In vivo, adult male C57BL/6J wild-type mice were used to produce a middle cerebral artery occlusion (MCAO) stroke model. On day three after reperfusion, obvious improvement in neurological scores, infarct volume reduction and cerebral edema amelioration were observed in meisoindigo treatment. Moreover, immunofluorescence staining and western-blot showed that the expression of NLRP3 inflammasome and its associated proteins in neurons and microglia was inhibited by meisoindigo. The effects of Meisoindigo on NLRP3 inflammasome inactivation and increased the M2 phenotype of microglia/macrophage through shifting from a M1 phenotype, which was possibly mediated by inhibition of TLR4/NF-κB. Furthermore, we verified the inhibitory effect of meisoindigo on TLR4/NF-κB signaling pathway, and found that meisoindigo treatment could significantly suppressed the expression of TLR4/NF-κB pathway-associated proteins in a dose-dependent manner, meanwhile, which resulted in downregulation of HMGB1 and IL-1β. Next, we established an in vitro oxygen glucose deprivation/Reperfusion (OGD/R) model in HT-22 and BV2 cells to simulate ischemic conditions. Cytotoxicity assay showed that meisoindigo substantially improved relative cell vitality and in HT-22 and BV2 cells following OGD/R in vitro. After suffering OGD/R, the TLR4/NF-κB pathway was activated, the expression of NLRP3 inflammasome-associated proteins and M1 microglia/macrophage were increased, but meisoindigo could inhibit above changes in both HT-22 and BV2 cells. Additionally, though lipopolysaccharide (LPS) stimulated the activation of TLR4 signaling in OGD/R models, meisoindigo co-treatment markedly reversed the upregulation of TLR4 and following activation of NLRP3 inflammasome and polarization of M1 microglia/macrophages mediated by TLR4. Overall, we demonstrate for the first time that meisoindigo post-treatment alleviates brain damage induced by ischemic stroke in vivo and in vitro experiments through blocking activation of the NLRP3 inflammasome and regulating the polarization of microglia/macrophages via inhibition of the TLR4/NF-κB signaling pathway.